Topics of Iraq in the Arab International Press - خضير سعد محمد (ALBAHITH ALALAMI, 2015)
The research entitled "the Iraqi Topics in International Arab Press" is an analytical study of two newspapers: Al-Arab and Al-Hayat published in London from September 1-30, 2013. The Arab press is one of the cultural monuments Home stretches for culture and media of Arabs outside the Arab Homeland which made them international press targeting public Arab audience’s not civil audiences in a particular country and formulating their contents on this basis taking into account intake affairs and issues that have been national or international. Because of this international presence of the Arab press, these newspapers have become one of the most influencing media in the formation of Arab public opinions. As a result of this, they have got their importance and drawing their roles in influencing the expatriate Arab reader. The researcher has used the descriptive approach as well as the way content is analyzed to extract the contents of the articles and reports in the newspapers of the sample down to the most accurate results. The sample papers have focused on the political topics first, then on the security issues because of their extreme importance on one side, and their relationship with the political process on the other. They have focused on articles and reports neglecting the other journalistic arts. Both study different issues especially those affecting the Iraqi society in general and Iraqi citizen in particular. The sources from which the sample newspapers have driven the Iraqi issues and affairs are Reuters, u.p.a., France Press Agency, and delegates. The number of writers who have written in Al-Hayat is 15 and in Al-Arab is 9 during the period of this research.